2005
DOI: 10.1098/rspb.2004.3023
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity of insect herbivores in tropical forests

Abstract: Studies of host specificity in tropical insect herbivores are evolving from a focus on insect distribution data obtained by canopy fogging and other mass collecting methods, to a focus on obtaining data on insect rearing and experimentally verified feeding patterns. We review this transition and identify persisting methodological problems. Replicated quantitative surveys of plant-herbivore food webs, based on sampling efforts of an order of magnitude greater than is customary at present, may be cost-effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
270
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(302 citation statements)
references
References 72 publications
12
270
3
4
Order By: Relevance
“…Th e most abundant plant species (i.e., those with most biomass or cover) tend to be related to a greater number of herbivore species ( Basset, 1991 ;Marques et al, 2000 ;Whitfeld et al, 2012 ) simply by having a greater probability of being found, that is, a greater apparency ( Feeny, 1976 ). However, in the particular case of tropical systems, where herbivorous insects are highly specialized to their host plants ( Novotny et al, 2002 ;Novotny and Basset, 2005 ;Ødegaard et al, 2005 ;Weiblen et al, 2006 ;Forister et al, 2012Forister et al, , 2015, it is likely that species strength is independent from the host plants biomass or abundance. In this case, plant resistance traits play an important role infl uencing herbivore preferences ( Coley and Barone, 1996 ;Stamp, 2003 ;Agrawal, 2005 ;Poelman et al, 2008 ) and thus their species strength, or their relative importance as food for herbivores.…”
Section: Study Site -Fieldwork Was Done At the Centro De Investigacionesmentioning
confidence: 94%
See 1 more Smart Citation
“…Th e most abundant plant species (i.e., those with most biomass or cover) tend to be related to a greater number of herbivore species ( Basset, 1991 ;Marques et al, 2000 ;Whitfeld et al, 2012 ) simply by having a greater probability of being found, that is, a greater apparency ( Feeny, 1976 ). However, in the particular case of tropical systems, where herbivorous insects are highly specialized to their host plants ( Novotny et al, 2002 ;Novotny and Basset, 2005 ;Ødegaard et al, 2005 ;Weiblen et al, 2006 ;Forister et al, 2012Forister et al, , 2015, it is likely that species strength is independent from the host plants biomass or abundance. In this case, plant resistance traits play an important role infl uencing herbivore preferences ( Coley and Barone, 1996 ;Stamp, 2003 ;Agrawal, 2005 ;Poelman et al, 2008 ) and thus their species strength, or their relative importance as food for herbivores.…”
Section: Study Site -Fieldwork Was Done At the Centro De Investigacionesmentioning
confidence: 94%
“…Th is discrepancy could be the result of diff erences in the degree of generalization between these types of networks; whereas networks of mutualistic interactions tend toward generalization ( Bascompte et al, 2006 ), plant-herbivore networks are highly specialized ( Prado and Lewinsohn, 2004 ;Cagnolo et al, 2011 ;López-Carretero et al, 2014 ). Th is specialization has developed from a complex set of ecological, biochemical and historical factors ( Ehrlich and Raven, 1964 ;Novotny et al, 2002 ;Novotny and Basset, 2005 ;Ødegaard et al, 2005 ;Weiblen et al, 2006 ;Gómez-Zurita et al, 2007 ) that, in general, have promoted interactions within subgroups of available plant species regardless of their coverage or density.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, parasitoids are a highly threatened group that is extremely vulnerable to extinction (Shaw & Hochberg, 2001; Smith, Wood, Janzen, Hallwachs, & Hebert, 2007). In temperate and tropical forests, the major source of insect diversity is the forest canopy (Novotny & Basset, 2005; Stork, 1988). Many arthropod species in temperate deciduous forests depend on canopy habitats, and approximately half of them are predators or parasitoids (Moran & Southwood, 1982; Ulyshen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although historically studies in terrestrial plant-animal interactions have focused on direct pairwise interactions, it is now acknowledged that generalization in interactions among species is more widespread than previously thought. This relatively high prevalence of generalist species has been highlighted in both mutualistic (Waser et al 1996) and trophic (Novotny & Basset 2005) interaction networks. Species generalism has some important consequences on the functioning and evolution of ecological systems, and the way we study them.…”
Section: Introductionmentioning
confidence: 99%
“…The explanatory variables were the interaction type, the total number of plants per web and the interaction term. We incorporated this covariate in the analyses because estimates of species generalism should indeed be considered with regard to the number of potentially available alternative plants (Novotny & Basset 2005). To test which part of the distribution differed, we then analysed each octave separately using linear models (gls function of nlme package) with the same model structure.…”
Section: (E) Statistical Analysesmentioning
confidence: 99%